2022
DOI: 10.3390/recycling7020014
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electrodialysis for the Selective Lithium Extraction Towards Cobalt, Nickel and Manganese from Leach Solutions Containing High Divalent Cations/Li Ratio

Abstract: The present work aims at investigating the potentialities of implementation of electrodialysis for the recycling of spent lithium-ion batteries. In this work, the use of highly-selective membrane toward lithium(I) in electrodialysis was investigated to recover selectively lithium(I) toward cobalt(II), nickel(II) and manganese(II) by means of monovalent ion-selective membranes. It was shown that the presence of divalent cations in the leach solution is responsible for a significant decrease of the limiting curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The composition of the synthetic leach solution was representative of leach solutions of NMC111 cathodic materials, i.e. 2.40 g L −1 lithium(I), 8.5 g L −1 cobalt(II), 8.9 g L −1 nickel(II), 4.6 g L −1 manganese(II) and 53 g L −1 sulfate [15]. The pH of the aqueous solutions containing the metal salts was adjusted at 2.8 by adding 0.1 mol L −1 sulfuric acid.…”
Section: Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of the synthetic leach solution was representative of leach solutions of NMC111 cathodic materials, i.e. 2.40 g L −1 lithium(I), 8.5 g L −1 cobalt(II), 8.9 g L −1 nickel(II), 4.6 g L −1 manganese(II) and 53 g L −1 sulfate [15]. The pH of the aqueous solutions containing the metal salts was adjusted at 2.8 by adding 0.1 mol L −1 sulfuric acid.…”
Section: Reagentsmentioning
confidence: 99%
“…Electrodialysis can also be used to extract metals from leaching solutions of cathode materials as mentioned previously. In our previous work [15], it was demonstrated that electrodialysis can be used to extract selectively and concentrate lithium from an aqueous solution containing cobalt(II), nickel(II), manganese(II) and lithium(I) in acidic sulfate solutions. However, the presence of divalent cations in the leach solution was responsible for metal hydroxide precipitation into the membrane porosity.…”
Section: Metal Recovery From Nmc Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane methods for separating the components of spent LIBs are still under development [ 1 ]. Selective electrodialysis (SED) is most commonly used to extract Li + ions from LIB leachates [ 15 , 16 , 17 , 18 ]. The SED technology differs from conventional electrodialysis in the use of multiple units of at least one special-grade ion-exchange membrane (cell pair).…”
Section: Introductionmentioning
confidence: 99%
“…They pass singly charged ions well and reject multiply charged ones. This makes it possible to efficiently separate Li + ions from Co 2+ , Ni 2+ and Mn 2+ [ 18 ].…”
Section: Introductionmentioning
confidence: 99%